The Effect of Psychological Capital and Perception of Organizational Support on Employee Performance at PTPN XXX - Dini Nur Afifah; Nina Nurani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of psychological capital and perceived organizational support on employee performance at PTPN XXX. The results of the study indicate that employee psychological capital is in the good category, perceived organizational support is quite good, and employee performance is considered good by employees. Partially, psychological capital has a significant influence on employee performance. Likewise, perceived organizational support partially has a significant influence on employee performance. These findings confirm the importance of psychological capital and perceived organizational support in improving employee performance.